Pengaruh Pembelajaran Daring terhadap Mental Healthy Mahasiswa Jurusan Akuntansi - Salsabila, Safitri; Syarif, Vandi Andiono; Rahmah, Ziyan Maulida; Nagari, Primasa Minerva (Universitas Pendidikan Indonesia, 2021)
The Corona Virus (Covid-19) pandemic is still ongoing from the beginning of March until now in Indonesia, seeing this the government immediately issued new policies such as carrying out activities at home for students from Early Childhood Education to Higher Education levels. The government does not recommend face-to-face learning (offline) and is replaced with online learning that can be done at home. This study aims to determine how much influence online learning has on the mental healthy of students majoring in accounting who are studying at the State University of Malang. The author conducted a study entitled